Translational minimal physiologically based pharmacokinetic model for transferrin receptor-mediated brain delivery of antibodies - Morris Muliaditan; Tamara J. van Steeg; Lindsay B. Avery; Wei Sun; Timothy R. Hammond; Diana Hijdra; Siak-Leng Choi; Nikhil Pillai; Nina C. Leksa; Panteleimon D. Mavroudis (mAbs, 2025)
Successful development of monoclonal antibodies (mAbs) for the treatment of central nervous system disorders has been challenging due to their minimal ability to cross the blood–brain barrier (BBB), resulting in poor brain exposure. Bispecific antibodies (bsAb) that bind to transmembrane protein expressed at the BBB, such as the transferrin receptor (TfR), have shown enhanced brain exposure in rodents and non-human primate (NHP) due to receptor-mediated transcytosis. However, it remains unclear how preclinical findings translate to humans. Moreover, optimal TfR binding affinity remains a subject of debate. Model-informed drug discovery and development is a powerful approach that has been successfully used to support research and development. The goal of this analysis was to expand a published brain minimal physiologically based pharmacokinetic (mPBPK) model to investigate the optimal TfR binding affinity for maximal brain delivery in NHP and to facilitate prediction of the PK of anti-TfR bsAbs in humans from NHP data. Literature data for plasma, cerebrospinal fluid (CSF), and brain exposure after administration of non-TfR mAbs and monovalent bsAbs with respect to TfR in NHP were used to develop the TfR mPBPK model. Clinical validation using human PK data from plasma and CSF for the monovalent anti-TfR bsAb trontinemab demonstrated good predictive performance without major model recalibration. The availability of the TfR mPBPK model is envisaged to provide better understanding of the relationship between TfR binding affinity, dose, and brain exposure, which would lead to more robust selection of lead candidates and efficacious dosing regimens.